The Owners and the Power: Insights from Annual General Meetings - Therese Strand (Copenhagen Business School (CBS), 2012)
This thesis consists of five empirical studies, all relating to shareholder activism at annual general meetings. The first study concerns the structure and content of general meetings in Denmark and Sweden comparatively. The paper reveals significant differences in the level of activism, with Swedish investors being the most active in terms of proposals, proxy voting, and `voice'. The paper takes a legal approach, and discusses divergence in activism levels from the perspective of shareholder prerequisites to engage in monitoring efforts. Further, the paper investigating the topics addressed through questions and opinions. The results show that matters which can be categorized as irrelevant are reasonably rare. This is an important finding, as suggestions to abolish general meetings have often been based on the assumption that general meetings facilitate nothing but irrelevant, time consuming, and costly discussions that serves no monitoring function. The second study analyses the impact of voting power on shareholder activism. We hypothesize that there is a positive relationship between shareholder activism and a measure of the largest shareholder's sensitivity to increased participation by small shareholders and find that firms' amenability to small shareholder influence leads to more proposals by the nomination committee, but fewer proposals by other shareholders. We interpret this as evidence that the shareholder elected nomination committees effectively channel shareholder concerns and preempt other kinds of activism. Politicians and companies that desire active shareholders could improve the amenability of firms to shareholder influence by ownership transparency, shareholder committees, and contacts with shareholder associations and other vehicles for collective action...
hdl:10398/8460
Keywords: 650